Laboratórios virtuais para o ensino de Química: a Pilha de Daniell em estudo - Urban, Mayara de Abreu (2024)
John Frederic Daniell (1790-1845), a Professor of Chemistry at King’s College, London, and Geology at the Honourable East India Company Military Seminary in Addiscombe, presented himself as an author of Meteorological Essays. He dedicated his efforts to the study of the involvement of electricity in chemical processes. Advocating for chemistry as an experimental science, Daniell emphasized the necessity for students to engage practically with proposed phenomena. Consequently, he intensified his exploration of electricity, focusing on developing a device with a more enduring electric current. Engaging with contemporary ideas, Daniell constructed a model of a cell that would later immortalize his name. This research scrutinizes the approach adopted by select textbooks in addressing the Daniell Cell, a recurrent topic in high school chemistry courses. Considering the pivotal role of practical experiments in chemistry education, the study deliberates on the contributions of both physical and virtual laboratories. These resources aim to assist students in mastering a subject that often elicits discomfort during the teaching and learning process